The Influence of Confirmation and E-Trust on E-Loyalty Through E-Satisfaction as a Mediating Variable: Evidence from Livin' by Mandiri Users - Fetri Mardyani; Azwardi; Iisnawati (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of Confirmation and E-Trust on E-Loyalty through E-Satisfaction among Livin’ by Mandiri users in Palembang. Using a quantitative explanatory design, data from 200 purposively selected active users were analyzed with PLS-SEM. Results show that Confirmation and E-Trust positively affect E-Satisfaction, while all three constructs positively influence E-Loyalty. E-Satisfaction partially mediates the effects of Confirmation and E-Trust on E-Loyalty. These findings extend Expectation-Confirmation Theory and highlight satisfaction as a key mechanism for strengthening loyalty in digital banking. Banks should therefore maintain reliable, secure, and expectation-consistent mobile services. Keywords: Confirmation; E-Trust; E-Satisfaction; E-Loyalty; Mobile Banking.